Proceedings of the 2016 Global Conference on Business, Management and Entrepreneurship 2016
DOI: 10.2991/gcbme-16.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Human Capital Performance in Developing Baitul Maal Wat Tamwil in Indonesia

Abstract: One of the problem in the development of Baitul Maal Wat Tamwil is human capital. It was due to the lack of BMT practitioners who understand the principles of good business management and sariah at once. Therefore, BMT as an Islamic Microfinance Institution is considered to be less competitive compared to other Islamic financial institutions or operating system which is not in line with Sariah compliance. Human capital is defined as the knowledge, skills and experience of workers which can be contributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…In accordance with the simple linear regression and T-test, it can be concluded that the human resource adequacy has positive and significant impact on the sustainability of BMT. This result is consistent with the previous studies, namely Nasution and Ahmed (2015), Nurasyiah et al (2016), Rusydiana andDevi (2013), andZubair (2016) regarding the positive impact of the human resource adequacy on the sustainability of BMT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with the simple linear regression and T-test, it can be concluded that the human resource adequacy has positive and significant impact on the sustainability of BMT. This result is consistent with the previous studies, namely Nasution and Ahmed (2015), Nurasyiah et al (2016), Rusydiana andDevi (2013), andZubair (2016) regarding the positive impact of the human resource adequacy on the sustainability of BMT.…”
Section: Discussionsupporting
confidence: 93%
“…Other than that, loose supervision and guidance reduces BMT competitiveness (Rusydiana & Devi, 2013). Moreover, Nurasyiah, Utami, Mahri, and Firmansyah (2016) further supported that an inadequate human resources of BMT is considered the main factor of the BMT competitive ability to be less power than the conventional counterpart. Then, inadequate human resource adequacy is one of the most challenging problems for BMT to be sustainable in a long time.…”
Section: Background Of Studymentioning
confidence: 90%
See 2 more Smart Citations
“…Due to budget constraint, human development training cannot be done that leads to the poor performance of human resources in BMT. This issue causes many BMTs to suffer bankruptcy problem because of operational failure [11]. Focusing on the case of BMT in Pekan Baru, the study supports that lack of quality human resource and absence of specific regulations affect its performance.…”
Section: A Human Capital Performancementioning
confidence: 61%